Либретто комических опер: 1840-1883 / [примечания А. И. Батюто] - Тургенев Иван Cергеевич (1986)
Экземпляры: ЧЗ (20160309) / Инвентарный номер: 19405 / Цена: 5.50 / Сис.шифр: Р1 / Авт.знак: Т 87 / ГРНТИ: 17 / ББК: 84(2Рос=Рус)1